The Application of Quantum Mechanics in Reactivity of Molecules - Sousa, Sérgio F. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Over recent decades, the increase in computational resources, coupled with the popularity of competitive quantum mechanics alternatives (particularly DFT), has promoted the widespread penetration of quantum mechanics calculations into a variety of fields targeting the reactivity of molecules. This book presents a selection of original research papers and review articles illustrating diverse applications of quantum mechanics in the study of problems involving molecules and their reactivity.